Recent Advances in the Applications of the Intramolecular Suzuki Cross-coupling Reaction in Cyclization and Heterocyclization: An Update - M. Heravi, Majid; Malmir, Masoumeh; Moradi, Razieh (Current Organic Chemistry, 2019)
The palladium-catalyzed reaction of aryl halide and boronic acid for the formation of C–C bonds so-called Suzuki–Miyaura cross-coupling reaction has many applications in Modern Synthetic Organic Chemistry. In 2013, we emphasized the applications of the intramolecular Suzuki cross-coupling reaction in cyclization and heterocyclization. Due to a plethora relevant papers appeared in the chemical literature, herein, we wish to cover by updating our previous review, the applications of the intramolecular Suzuki cross-coupling reaction in cyclization and heterocyclization leading to various homocyclic and heterocyclic compounds reported during a period of 2013 to 2018.
Keywords: Pd-catalyzed reactions